Effects of atopy and rhinitis on exhaled nitric oxide values - a systematic review - Linhares, D (2014)
BACKGROUND: Atopy and rhinitis are among the factors affecting exhaled nitric oxide (FeNO) values and may contribute to difficulties in the clinical interpretation of FeNO measurements. However, data assessing their effects on FeNO values had never been summarized. This review aims to evaluate the effect of atopy and rhinitis in FeNO values in otherwise healthy individuals. METHODS: A systematic review was performed in Pubmed, Scopus and ISI Web of Knowledge. A two-step selection process was completed, and from 2357 references 19 were included. The inclusion criteria were: participants without known diseases other than rhinitis; atopy assessement by SPT or Specific IgE; and FeNO measurements according to ATS/ERS recommendations. RESULTS: The 8 articles measuring FeNO in children showed higher values in both allergic rhinitis and atopic children when compared with healthy children. The 11 articles performed in adults observed higher FeNO in AR patients comparatively with either healthy or atopic individuals. However, adult healthy and atopic individuals had similar FeNO values. CONCLUSIONS: FeNO values are higher in individuals with rhinitis and/or atopy without other health problems. These effects are small, seem to be independent and should be further studied using multivariate models. The effect of atopy was observed only in children. The combined effect of atopy and rhinitis produced higher FeNO values in adults. These results support that both atopy and rhinitis should be considered when interpreting or when defining FeNO reference values.